A Novel Ultrawideband Planar Inverted-F Antenna with Capacitive Ground Plane - Haixia Liu; Fei Wang; Yang Yang; Xiaowei Shi; Long Li (International Journal of Antennas and Propagation)
With the trend of the miniaturization, broadband, and integration of multisystems of wireless communication terminals, a new ultrawideband planar inverted-F antenna (PIFA) with capacitive ground plane is proposed in this paper. The capacitive ground plane is composed of a sheet of metal islands, which makes a major contribution to ultra-wideband from 2.3 GHz to 9.0 GHz by applying the capacitive compensation for input impedance of the PIFA in high-order modes frequency bands. The effect of geometric parameters of capacitive ground plane and antenna height on antenna performance is analyzed. It is found that the radiation pattern in free space and the gain of the proposed antenna also meet the demands of the wireless communication terminals. The reported antenna was fabricated and measured, and the experimental results are in good agreement with the simulation results.